Nitrogen Fixation by Thermophilic Blue-Green Algae (Cyanobacteria): Temperature Characteristics and Potential Use in Biophotolysis - Miyamoto, Kazuhisa (1979)
Thermophilic, nitrogen-fixing, blue-green algae (cyanobacteria) were investigated for use in biophotolysis. Three strains of Mastigocladus laminosus were tested and were found to be equally effective in biophotolysis as judged by nitrogenase activity. The alga, M. laminosus NZ-86-m, which was chosen for further study, grew well in the temperature range from 35 to 50°C, with optimum growth at 45°C, at which temperature acetylene reduction activity was also greatest. The maximum tolerable temperature was 55°C. Acetylene reduction activity was saturated at a light intensity of 1 × 10(4) ergs cm(−2) s(−1). Atmospheric oxygen tension was found to be slightly inhibitory to acetylene reduction of both slowly growing and exponentially growing cultures. Nonsterile continuous cultures, which were conducted to test problems of culture maintenance, could be operated for 2 months without any significant decrease in nitrogenase activity or contamination by other algae. Nitrogen-starved cultures of M. laminosus NZ-86-m produced hydrogen at comparable rates to Anabaena cylindrica. The conversion efficiency of light to hydrogen energy at maximum rates of hydrogen production was 2.7%.